Assessment Isoproteic Using Sorghum Grain Diets in Rearing Calves (Veterinary Science, 2017)
In this study the technical and economic feasibility of using ground sorghum grain in diets for breeding isoproteic to corral British breed calves tested. They were grouped by body weight and assigned to three treatments (T) based on grain sorghum (GS) with different protein sources for 80 days: Grain sorghum (57.96%) with Sunflower Pellet (G) (32, 04%) TI (GSG); Grain sorghum (67.95%) with Pellet soy (S) (22.05%) TII (GSS); Grain sorghum (3.87%) with wheat bran (A) (86.13%) TIII (GSA). The intake of dry matter (DM) had significant differences (P
Keywords: feedlot; rearing; calves; nutrition; sorghum